Assessment of air pollution in the conurbation of Munich: present and future. (12th January 2010) - Suppan, Peter
Traffic emissions have a severe impact to the environment with all its socio-economic consequences in urban conglomerations. Traffic emissions will still increase in the future, whereas other categories of emissions will decrease within the next years. Numerical simulations are a useful tool to assess the effect of different emissions on the regional air quality of primary and secondary pollutants. Results of a fully coupled Meteorology Chemistry Dispersion Model (MCCM) are presented. Within the project MOBINET the increasing mobility until 2010 shall be managed with the introduction of new forms of mobility services, innovative traffic technologies and multimodal traffic management.